The past from above aerial photographs of archaeological sites - Gerster, Georg 1928-2019 (Paul Getty Museum, 2005)
Catalog for an exhibition at the Ruhrlandmuseum in Essen, honoring Georg Gerster for over 40 years of aerial photography of archaeological sites around the world.
Keywords: Gerster, Georg <1928-> - Expositions; Gerster, Georg <1928-> -- Exhibitions; Ruhrlandmuseum Essen - Expositions; Ruhrlandmuseum Essen -- Exhibitions; Photographie aérienne en archéologie - Expositions; Aerial photography in archaeology -- Exhibitions; Ausstellungskatalog